Extraction of microalgal oil from Nannochloropsis oceanica by potassium hydroxide-assisted solvent extraction for heterogeneous transesterification. (December 2020) - Park, Ji-Yeon; Kim, Min-Cheol; Cheng, Jun; Yang, Weijuan; Kim, Deog-Keun
Abstract: The feasibility of potassium hydroxide for simultaneous removal of chlorophyll during solvent extraction from wet microalgae (200 g/L) was evaluated. Extracted oil was converted to biodiesel by ZSM-5-based heterogeneous catalysts. The total oil (fatty acid-based) content of Nannochlorposis oceanica cultivated in open raceway ponds was 19.5%. The oil recovery yields from dry and wet microalgae using hexane were 44.4 and 11.8%, respectively, whereas using a hexane-methanol mixture were increased to 79.3 and 74.8%, respectively. For the heterogeneous transesterification of microalgal oil extracted by the hexane-methanol mixture from wet microalgae, the fatty acid methyl ester (FAME) contents were 2.3, 48.3, and 4.7% of product recovered after reaction for ZSM-5, Na/ZSM-5, and SO4 2− /ZSM-5, respectively; by the potassium hydroxide-assisted process, the corresponding FAME contents were increased to 21.9, 86.2, and 86.0%, respectively, due to improvement of the oil properties by the decrease of the chlorophyll content. Through the addition of potassium hydroxide, chlorophyll was effectively removed from oil, and eventually, the biodiesel conversion was sharply increased with heterogeneous Na/ZSM-5 and SO4 2− /ZSM-5 catalysts. Graphical abstract: Image 1 Highlights: Enhancement of extraction efficiency from wet microalgae by hexane-methanol mixture. Removal of chlorophyll from N. oceanica by KOH-assisted hexane-methanol extraction. Conversion of microalgal oil to biodiesel by Na/ZSM-5 and SO4 2− /ZSM-5 catalysts. Enhancement of heterogeneous transesterification by chlorophyll removal from oil. Successful application of heterogeneous catalysts for microalgal biodiesel production.